Experiences of burnout among adolescent female gymnasts: Three case studies - Dubuc, N. G.; Schinke, R. J.; Eys, M. A.; Battochio, R.; Zaichkowsky, L. (Journal of Clinical Sport Psychology, 2010)
Within the current study, the process of adolescent burnout is considered in relation to perceived contributors, symptoms, consequences, and subsequently, effective and ineffective coping strategies. Through case studies, the researchers sought the burnout experiences of three competitive female gymnasts. Participants were selected based on scores obtained from Raedeke and Smith`s (2001) Athlete Burnout Questionnaire. To gain a comprehensive understanding of the process, athlete data were considered in tandem with interviews from at least one parent and one coach. Transcribed data were segmented into meaning units, coded into a hierarchy of themes and verified by each respondent. Despite common trends among the participants, differences were also found in relation to symptoms, contributors, and the progression of the condition. Implications are provided for the athlete/parent/coach triad and also for sport psychologists.